Hubungan antara Work-Family Conflict dan Neuroticsm dengan Work Engagement dan Burnout Pada Guru - Christina Maria Indah Soca Retno Kuntari (Humanitas (Jurnal Psikologi), 2022)
This study aims to determine the relationship between Work-Family Conflict, Neuroticism with Work Engagement, and Burnout in teachers. Work-family conflict is a conflict between roles in work and family. The neurotic personality trait has personality traits that are easily anxious, temperamental, self-pitiful, emotional, prone to stress, and sensitive to criticism. Work engagement is a positive state of mind, while burnout is psychological fatigue that arises due to conflict or pressure at work. A purposive sampling technique was used in this study. The respondents of this study consisted of 108 high school teachers. The results of this study indicate that work-family conflict and neurotic personality have a negative relationship with work engagement. This study found that there was no relationship between work-family conflict and burnout. Furthermore, no relationship was found between neuroticism and burnout in high school teachers.